Is muscle activation diverse in females with isolated patellofemoral osteoarthritis contrasted with age-matched healthy controls during stair descent task? - Adel, Jilan; Hamoda, Reham E.; Mohamed, Ayah Mahmoud; Balbaa, Alaa Eldin; Neamat Allah, Neama H.; Hamada, Hamada Ahmed (Frontiers in Physiology, 2024)
Background: Patellofemoral osteoarthritis (PF OA) is exceptionally predominant and limiting. However, little is known about the risk factors that contribute to its onset and progression. Purpose: to decide if females with PF OA descend stairs using different muscular activation strategies contrasted than similarly aged healthy controls. Methods: Thirty-one females with isolated PF OA and 11 similarly aged healthy females took part in this study. The activation onset and duration of vastus medialis obliques (VMO), vastus lateralis (VL), gluteus Medius (GM), transversus abdominus (TrA), and multifidus muscles were evaluated during stair descent task using surface electromyography (EMG). Results: There was a non-significant difference between females with PF OA and controls regarding all tested variables except for the GM activation onset that was significantly delayed in females with PF OA as p-value equaled 0.011. Conclusion: The causes of PF OA differ and might not always be due to a lack of quadriceps strength or VMO activation deficiency and Prospective longitudinal studies are required to confirm this assumption.